Enhancing Reactive Power Compensation in Distribution Systems through Optimal Integration of D-STATCOM using the Pelican Optimization Algorithm - A. F. S. Yussif; T. Seini; B. Ayasu; E. A. Nyantakyi (International Journal of Electrical Engineering and Applied Sciences)
This paper presents a study that introduces the Pelican Optimization Algorithm (POA) as an innovative approach for the strategic deployment of Distribution Static Synchronous Compensators (D-STATCOM) in distribution systems. The primary objectives are to reduce losses and enhance voltage profiles in radial distribution systems. The proposed approach is validated on both the IEEE 33-bus and IEEE 69-bus systems through comprehensive simulations using MATLAB software. The results demonstrate exceptional performance, showcasing a remarkable 29.40% and 32.30% reduction in active power losses for the respective systems. Furthermore, a comparative analysis against recent methods from the literature highlights the superior efficacy of the POA algorithm, revealing reductions of 29.15% and 32.00% in active power losses for the IEEE 33-bus and IEEE 69-bus systems. These findings substantiate the efficiency of the POA algorithm in strategically positioning and sizing D-STATCOM, making significant strides toward minimizing losses and improving voltage profiles in distribution systems. In summary, this study provides valuable insights into the field of power systems optimization, offering a pioneering solution for the effective deployment of D-STATCOM to enhance the overall performance of distribution networks.